Porang Plant Commodity Development Strategy - Izna Asmi; Darwis Darwis; Sri Hardianti Rosadi; Fitry Purnamasari (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2023)
Porang plants are one of the plants worth developing because of their high economic value, apart from that, the contents of porang tubers are also used in the food and health industries. This research was carried out at PT Al Fatih Porang in Sidrap Regency. The aim of this research is to look at the Porang Plant Commodity Development Strategy in Talumae Village, Watang Sidenreng District, Sidrap Regency.The methods used in this research are qualitative and quantitative research methods. The population used in this research were employees of PT Al Fatih Porang in Sidrap Regency, South Sulawesi. The sample size was 50 employees selected purposively. Data collection techniques use interviews, observation, questionnaires. In this research, researchers used SWOT data analysis to look at the Porang Commodity development strategy at PT Al Fatih Porang, Sidrap Regency. The SWOT matrix is a tool for matching external and internal key factors. The research results show that PT Al Fatih Porang has an IFAS strength value of 1.84 which is greater than the Weakness value, namely 1.66. The EFAS Opportunity value is 2.57, which shows that the opportunity value is greater than the threat value, namely 0.68. PT Al Fatih Porang is in Quadrant I so alternative development strategies that can be implemented are utilizing farmers' experience to manage existing land in order to meet the increasing demand for porang from industry and utilizing seed and fertilizer production facilities to produce good quality and quantity of porang so that can achieve the maximum porang price.